Thomas Cromwell: Friend or Foe of the English Nobility: An Analysis of Thomas Cromwell's Character in Hilary Mantel's Historical Fiction (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Cromwell is smart, persuasive, and shrewd in the court setting. Wolf Hall, Bring Up the Bodies,and The Mirror The Light , Hilary Mantel's books about life in king Henry's court as seen by ThomasCromwell, are widely regarded as having revitalized the historical fiction genre. While Mantel has beenlauded for her portrayal of Cromwell, she has also been criticized for painting him in too rosy a light.